1980
DOI: 10.1037/0033-2909.87.1.195
|View full text |Cite
|
Sign up to set email alerts
|

Stereotyping: From prejudice to prediction.

Abstract: A brief review of stereotype research indicates that little has been discovered about stereotypes that are defined as bad generalizations and measured with the Katz and Braly checklist. McCauley and Stitt have proposed that stereotypes can be better understood as probabilistic predictions that distinguish one group from another. The practicality of the proposed diagnostic-ratio measure of stereotyping is argued, and the relation of the new measure to the Katz and Braly measure is discussed. Lippmann's argument… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
161
0
3

Year Published

1985
1985
2009
2009

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 318 publications
(174 citation statements)
references
References 32 publications
7
161
0
3
Order By: Relevance
“…Following recent theoretical work within social psychology, we assume that social stereotypes are probabilistic generalizations or predictions about the attributes of a social category or group (Brigham, 1971;Judd & Park, 1993;McCauley, Stitt, & Segal, 1980). These probabilistic generalizations might, but might not, accurately reflect the state of affairs in the real world.…”
mentioning
confidence: 99%
“…Following recent theoretical work within social psychology, we assume that social stereotypes are probabilistic generalizations or predictions about the attributes of a social category or group (Brigham, 1971;Judd & Park, 1993;McCauley, Stitt, & Segal, 1980). These probabilistic generalizations might, but might not, accurately reflect the state of affairs in the real world.…”
mentioning
confidence: 99%
“…Stereotypes thus contain the standard assumptions that one makes about members of that category (McCauley et al, 1980). The use of stereotypes in computer systems that maintain models of their users was introduced by Rich with the system GRUNDY (Rich, 1979(Rich, , 1983.…”
Section: Stereotype Reasoningmentioning
confidence: 99%
“…Pettigrew, 1979). Other research has focused on how own group biases influence predictions of other's behaviour (McCauley, Stitt, & Segal, 1980;Jackson, Sullivan, & Hodge, 1993). Few studies, however, have examined evaluations, attributions, and predictions within one study (Jackson et al, 1993), and even fewer have examined whether these biases are found in children.…”
Section: Introductionmentioning
confidence: 99%